ChemInform Abstract: CO Extrusion in Homogeneous Gold Catalysis: Reactivity of Gold Acyl Species Generated Through Water Addition to Gold Vinylidenes. Issue 24 (June 2015) - Bucher, Janina; Stoesser, Tim; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract: A novel reactivity of gold vinylidenes is discovered through the addition reaction of water to gold vinylidene intermediates resulting in CO‐extrusion and cyclization to indenes.